Lithological and structural control on Italian mountain geoheritage: opportunities for tourism, outdoor and educational activities - Bollati, Irene; Coratza, Paola; Panizza, Valeria; Pelfini, Manuela (Quaestiones Geographicae, 2018)
Mountain landscapes are generated by the interplay of endogenous and exogenous processes, whose reciprocal importance changes over times. The Italian relief reflects a high geomorphodiversity and an overview on iconic mountain landscapes, representative of the lithological-structural diversity of the Italian relief, is presented. The study cases, located along Alps and Apennines and in the Sardinia island, are exemplary for the comprehension of the role of the substratum in shaping mountain landscapes and of the deriving risk scenario. Moreover, mountain landscapes are characterized by a high potential for use in terms of: i) ideal open-air natural laboratories for multidisciplinary educational purposes including geological-geomorphological, historical and ecological topics; ii) possibility of specific outdoor activities that take advantage of outdoor sports (e.g., climbing, canyoning, speleology). These feasible and versatile opportunities favour the enhancement of such environments under different perspectives as well as the involvement of local communities and the socio-economic return deriving from mountain geoheritage management.